Strain-Induced Gauge Field and Landau Levels in Acoustic Structures - Yang, Zhaoju (2017)
The emerging field of topological acoustics that explores novel gauge-field-related phenomena for sound has drawn attention in recent years. However, previous approaches constructing a synthetic gauge field for sound predominantly relied on a periodic system, being unable to form a uniform effective magnetic field, thus lacking access to some typical magnetic-induced quantum phenomena such as Landau energy quantization. Here we introduce strain engineering, previously developed in graphene electronics and later transferred to photonics, into a two-dimensional acoustic structure in order to form a uniform effective magnetic field for airborne acoustic wave propagation. Landau levels in the energy spectrum can be formed near the Dirac cone region. We also propose an experimentally feasible scheme to verify the existence of acoustic Landau levels with an acoustic measurement. As a new freedom of constructing a synthetic gauge field for sound, our study offers a path to previously inaccessible magneticlike effects in traditional periodic acoustic structures.